Three-year-olds' understanding of the consequences of joint commitments. - Maria Gräfenhain (Public Library of Science (PLoS), 2013)
Here we investigate the extent of children's understanding of the joint commitments inherent in joint activities. Three-year-old children either made a joint commitment to assemble a puzzle with a puppet partner, or else the child and puppet each assembled their own puzzle. Afterwards, children who had made the joint commitment were more likely to stop and wait for their partner on their way to fetch something, more likely to spontaneously help their partner when needed, and more likely to take over their partner's role when necessary. There was no clear difference in children's tendency to tattle on their partner's cheating behavior or their tendency to distribute rewards equally at the end. It thus appears that by 3 years of age making a joint commitment to act together with others is beginning to engender in children a "we"-intentionality which holds across at least most of the process of the joint activity until the shared goal is achieved, and which withstands at least some of the perturbations to the joint activity children experience.